2018
DOI: 10.1007/s00705-017-3700-y
|View full text |Cite
|
Sign up to set email alerts
|

Regional, age and respiratory-secretion-specific prevalence of respiratory viruses associated with asthma exacerbation: a literature review

Abstract: Despite increased understanding of how viral infection is involved in asthma exacerbations, it is less clear which viruses are involved and to what extent they contribute to asthma exacerbations. Here, we sought to determine the prevalence of different respiratory viruses during asthma exacerbations. Systematic computerized searches of the literature up to June 2017 without language limitation were performed. The primary focus was on the prevalence of respiratory viruses, including AdV (adenovirus), BoV (bocav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 34 publications
(36 reference statements)
2
145
3
4
Order By: Relevance
“…In this study, RV (48%) was the most detected virus among subjects with asthma exacerbation followed by RSV (6%), and the age on admission was significantly higher in the RV group than in the RSV group. The detection frequency of RV and RSV in our study was consistent with that in previous reports on the relationship between causative viruses and exacerbation in asthmatic patients, suggesting that our study illustrates the actual virus prevalence associated with asthma exacerbation . Heymann et al reported prevalence of rhinovirus infection was much less in the wheezing patients aged <3 years compared to those above the age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, RV (48%) was the most detected virus among subjects with asthma exacerbation followed by RSV (6%), and the age on admission was significantly higher in the RV group than in the RSV group. The detection frequency of RV and RSV in our study was consistent with that in previous reports on the relationship between causative viruses and exacerbation in asthmatic patients, suggesting that our study illustrates the actual virus prevalence associated with asthma exacerbation . Heymann et al reported prevalence of rhinovirus infection was much less in the wheezing patients aged <3 years compared to those above the age.…”
Section: Discussionsupporting
confidence: 91%
“…Respiratory viral infections are associated with the pathophysiology of childhood asthma exacerbation . The major pathogens involved are human rhinovirus (RV), respiratory syncytial virus (RSV), enterovirus (EV), influenza virus, and human metapneumovirus (hMPV) . In previous studies, RSV has been associated with wheezing during infancy, whereas RV has been detected more frequently in school‐age children with wheezing .…”
Section: Introductionmentioning
confidence: 99%
“…25 Although hMPV causes wheezing and lower respiratory tract symptoms, the contribution of hMPV to asthma exacerbations varies among different populations. In those with asthma exacerbations, the detection rate of hMPV is approximately 5% worldwide, 4 whereas in those with hMPV LRTI a much higher proportion have a diagnosis of asthma. In a study of children with hMPV LRTIs in the United States, 14% to 33% carried a diagnosis of asthma or history of wheezing.…”
Section: Human Bocavirusmentioning
confidence: 99%
“…It has long been identified as a precipitant of asthma exacerbations in all age groups. 2,4,45 In people with asthma exacerbations, the detection rate of influenza virus is approximately 10% worldwide, 4 but, during a flu season, the prevalence of influenza viruses can be as high as 20% in wheezing infants and 20% to 25% in adults with acute asthma exacerbations. 2,46,47 Although involvement of influenza virus is common in asthma exacerbation, influenza virus is an infrequent cause of acute wheezing illness in younger children.…”
Section: Influenza Virusmentioning
confidence: 99%
See 1 more Smart Citation